2019
DOI: 10.1055/s-0039-1677812
|View full text |Cite
|
Sign up to set email alerts
|

Revision Single-Stage Anterior Cruciate Ligament Reconstruction Using an Anterolateral Tibial Tunnel

Abstract: Revision anterior cruciate ligament (ACL) reconstruction is a technically demanding enterprise. Management of widened or previously malpositioned tunnels is challenging and often requires innovative approaches. The purpose of this study was to evaluate the function and clinical results of revision single-stage ACL surgery using an anterolateral tibial tunnel (ALTT). A consecutive series of knees with arthroscopic ACL revision surgery were analyzed prospectively between April 2012 and September 2015. Among the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…In the literature on ACL revision, researchers primarily focus on the recovery of knee function, surgical strategies, and relevant techniques [ [31] , [32] , [33] , [34] , [35] ]. Regrettably, the assessment of patients' psychological recovery is often overshadowed [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the literature on ACL revision, researchers primarily focus on the recovery of knee function, surgical strategies, and relevant techniques [ [31] , [32] , [33] , [34] , [35] ]. Regrettably, the assessment of patients' psychological recovery is often overshadowed [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…[ 8 ] concluded that it is possible to use an anterolateral tunnel in the tibia with adequate knee stability to avoid an eventual medial defect, and a clinical study by Keyhani et al. [ 15 ] with 25 patients also showed promising results in the case of the first ACL revision. Some authors have studied the benefit of performing reconstruction with a lateral tibial tunnel for PCL reconstruction for reasons other than enlarged tunnels [ 14 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Inclusion criteria were [11][12][13] : 1. unilateral ACL injury of the knee; 2. grade I or II injury of the meniscus; 3. Outbridge grade I-II injury of the knee cartilage;…”
Section: Methodsmentioning
confidence: 99%